2016
DOI: 10.1177/2156587216629041
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Evaluation of Intervention by a Medical Clown Visit or by Viewing a Humorous Film Following In Vitro Fertilization and Embryo Transfer

Abstract: This study compared responses to an in-person clown visit and a humorous film following in vitro fertilization and embryo transfer. Intervention was a 10-minute clown visit (n = 101) or 10-minute humorous video clip (n = 99). Demographic and fertility-related data and preintervention anxiety scores were collected. Participants completed an Evaluation of Intervention form postintervention. There were no group differences on demographic or fertility-related data or anxiety scores. Findings indicate while partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Medical clowns (MCs), also called hospital clowns or clown doctors, are trained professionals who aim to change the perception of the hospital environment by creating humoristic situations to elicit laughter and joy in children’s wards as well as with adults and older adults ( Dionigi et al, 2014 ; Dionigi & Goldberg, 2019 ; Friedler et al., 2017 ; Koller & Gryski, 2008 ; Lalantika & Yuvaraj, 2020 ; Linge, 2008 ; Ofir et al, 2016 ; Weaver et al, 2007 ). In many cases, patients, families, and staff value MCs ( Dionigi & Canestrari, 2016 ; Higueras et al, 2006 ; Schwebke & Gryski, 2003 ; Warren & Spitzer, 2013 ), especially for improving patients’ physical and mental well-being through creating an alternative atmosphere ( Dionigi et al, 2014 ; Friedler et al, 2017 ; Lopes-Júnior et al, 2020 ; Nuttman-Shwartz et al, 2010 ; Weaver et al, 2007 ). Medical clowns entertain patients during recovery ( Dionigi & Canestrari, 2016 ; Koller & Gryski, 2008 ; Ofir et al, 2016 ), and reduce anxiety, distress, and pain during acute care and invasive examinations ( Finlay et al, 2014 ; Friedler et al, 2017 ; Kristensen et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medical clowns (MCs), also called hospital clowns or clown doctors, are trained professionals who aim to change the perception of the hospital environment by creating humoristic situations to elicit laughter and joy in children’s wards as well as with adults and older adults ( Dionigi et al, 2014 ; Dionigi & Goldberg, 2019 ; Friedler et al., 2017 ; Koller & Gryski, 2008 ; Lalantika & Yuvaraj, 2020 ; Linge, 2008 ; Ofir et al, 2016 ; Weaver et al, 2007 ). In many cases, patients, families, and staff value MCs ( Dionigi & Canestrari, 2016 ; Higueras et al, 2006 ; Schwebke & Gryski, 2003 ; Warren & Spitzer, 2013 ), especially for improving patients’ physical and mental well-being through creating an alternative atmosphere ( Dionigi et al, 2014 ; Friedler et al, 2017 ; Lopes-Júnior et al, 2020 ; Nuttman-Shwartz et al, 2010 ; Weaver et al, 2007 ). Medical clowns entertain patients during recovery ( Dionigi & Canestrari, 2016 ; Koller & Gryski, 2008 ; Ofir et al, 2016 ), and reduce anxiety, distress, and pain during acute care and invasive examinations ( Finlay et al, 2014 ; Friedler et al, 2017 ; Kristensen et al., 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, patients, families, and staff value MCs ( Dionigi & Canestrari, 2016 ; Higueras et al, 2006 ; Schwebke & Gryski, 2003 ; Warren & Spitzer, 2013 ), especially for improving patients’ physical and mental well-being through creating an alternative atmosphere ( Dionigi et al, 2014 ; Friedler et al, 2017 ; Lopes-Júnior et al, 2020 ; Nuttman-Shwartz et al, 2010 ; Weaver et al, 2007 ). Medical clowns entertain patients during recovery ( Dionigi & Canestrari, 2016 ; Koller & Gryski, 2008 ; Ofir et al, 2016 ), and reduce anxiety, distress, and pain during acute care and invasive examinations ( Finlay et al, 2014 ; Friedler et al, 2017 ; Kristensen et al., 2018 ). Furthermore, MCs assist in coping with chronic and terminal illness by improving quality of life and decreasing fear ( Nuttman-Shwartz et al, 2010 ; Warren & Spitzer, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…week intervention [84]. Quality of life, and cognitive function improved in cancer patients (n = 56), and pain reduced in a randomized control trial using laughter therapy [86]; with similar effects reported in research using 12 sessions of laughter therapy in nursing residents over four week intervention [87].…”
Section: Psychological: Laughter Researchmentioning
confidence: 54%
“…A systematic review found the use of humour in palliative interventions to be beneficial (k = 13, n = 759) [39]. Clown interventions reduced stress and anxiety in hospitalised children and their parents [35] (k = 18, n = 1,444), and in women undergoing in vitro fertilization (n = 295) [84]. The use of humour as a coping mechanism is often highlighted: it was found to be effective with positive humour, but not with negative humour [149].…”
Section: Psychological: Humour Researchmentioning
confidence: 99%
“…Bir çalışmada, yaşlı demans hastalarına bu müdahale 10 haftalık periyod halinde uygulanmış ve çalışma sonucunda sosyal etkileşimde iyileşme görülmüştür (28) . Diğer bir çalışmada ise, kısırlık tedavisi ve embriyo transferi yapılacak kişilere uygulanmış, anksiyete düzeyini daha aza indirgemesi ve bunun sonucunda tedavi sürecine olumlu katkısı olması nedeniyle müdahale hakkında pozitif görüş bildirmişlerdir (29) .…”
Section: Introductionunclassified